A non-invasive method based on saliva to characterize transthyretin in familial amyloidotic polyneuropathy patients using FT-ICR high-resolution MS - Costa, Gonçalo da (2012)
Copyright © 2010 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim